REMOTE 3-YEAR RESULTS OF APPLICATION OF «INDIRECT» WAYS OF REVASCULARIZATION IN PATIENTS WITH CHRONIC ISCHEMIA OF LOWER EXTREMITIES - Yu. V. Chervyakov; I. N. Staroverov; A. V. Borisov; E. G. Nersesyan; O. N. Vlasenko; S. N. Lavlinskiy (Вестник хирургии имени И.И. Грекова)
There are several ways of «indirect» revascularization such as revascularizated osteotrepanation of shinbone and lumbar sympathectomy (LS) for treatment of patients with chronic ischemia of lower extremities. They appeared to be sufficiently effective for the patients with II stage of the disease. Patients with critical ischemia (III stage) had persistent positive results after lumbar sympathectomy during 3-year period only in 33% of cases and using revacularized osteotrepnation - 46%. The difference in efficacy of treatment using LS and standard conservative therapy is statistically low significant, so that isn’t allowed recommending the sympathectomy for treatment of III stage ischemia. The method of revascularizated osteotrepanation of shinbone showed a reliably better result, therefore this way is reasonable to apply in surgery in case of III stage ischemia.